Onset of obesity in a 36 year birth cohort study. Issue 6542 (2nd August 1986) - Braddon, F E; Rodgers, B; Wadsworth, M E; Davies, J M
Abstract : A large national cohort of children studied from birth to 36 years was used to test the predictive value of childhood obesity for obesity in adult life. Only 21% (39) of obese 36 year olds had been obese at age 11 years, and even when associated social factors were taken into account the correctly predicted percentage was much lower than the prediction rate achieved using body mass data from age 26 years. The comparatively poor predictive value of childhood obesity and the association of adult obesity with educational achievements and socioeconomic circumstances of family of origin emphasise the need for encouraging good nutritional and exercise habits rather than placing undue emphasis on the control of childhood obesity.